Analisis Pasang Surut dan Model Numerik Arus pada Perairan Laut Destinasi Wisata Hutan Mangrove Tongke-Tongke Kabupaten Sinjai (TIDAL ANALYSIS AND NUMERICAL MODELS OF SEA CURRENT IN TONGKE-TONGKE MANGROVE FOREST TOURISM DESTINATION SINJAI DISTRICT) - Andi Imran Anshari; Irawan Alham (Fakultas Pertanian, Universitas Syiah Kuala, 2023)
The Tide Survey was conducted to determine the types of tides and tides around the Tongke-tongke Mangrove Forest Tourism Destination. The results of this study are expected to provide an overview of the test results in the field with the results of numerical tests on the data to be processed. The research was conducted from August to October 2020 in the waters of the Tongke-tongke Mangrove Forest Tourism Destination. The method used is quantitative. Tidal data collection for 15 days at the study location. While the current measurement is carried out twice, namely at the highest (spring tide) and lowest (neap tide) tide and the data presentation is displayed with SMS 10.0 software (Surface water modeling system). From the results of the tide study, it was found that the tide type in the Tongke-tongke Mangrove Forest Tourism Destination is mixed tide, tilted double daily (mixed tide prevailing semi diurnal). In 1 day there are 2 times the tide and 2 times the ebb with ¬ different heights with the tide of 1.36 m. Whereas in the analysis of SMS software.10, where at low tide, the dominant current moves from east to west with an average speed of 0.0067 m / sec and at high tide around the study area the flow moves from west to east the average is 0.0035 m / sec. The average velocity of the current before high tide is greater than that of the low tide, and the implementation of the results of the study of flows and tides of the Tongke-tongke Mangrove Forest Tourism Destination illustrates that the condition of this mangrove forest is very dependent on the natural conditions of currents and tides in supporting the growth and density of mangroves